Zingiber mekongense Gagnep. (Zingiberaceae): A new Distribution Record for the Flora of Vietnam - Le, Thi Huong (H. : ĐHQGHN, 2020)
Zingiber mekongense Gagnep., which found in the Central Vietnam, is here reported as a new record for the flora of Vietnam. Voucher specimens collected in the Binh Thuan, Nghe An and Thanh Hoa provinces and deposited in the major herbaria: the herbarium of the Biology (Vinh University), HN, VNM. A detailed morphological description and a coloured photographs of this species along with data on distribution, ecology, phenology and notes to its allies are given.